The Ctp Type IVb Pilus Locus of Agrobacterium tumefaciens Directs Formation of the Common Pili and Contributes to Reversible Surface Attachment - Wang, Yi (American Society for Microbiology, 2014)
Agrobacterium tumefaciens can adhere to plant tissues and abiotic surfaces and forms biofilms. Cell surface appendages called pili play an important role in adhesion and biofilm formation in diverse bacterial systems. The A. tumefaciens C58 genome sequence revealed the presence of the ctpABCDEFGHI genes (cluster of type IV pili; Atu0216 to Atu0224), homologous to tad-type pilus systems from several bacteria, including Aggregatibacter actinomycetemcomitans and Caulobacter crescentus. These systems fall into the type IVb pilus group, which can function in bacterial adhesion. Transmission electron microscopy of A. tumefaciens revealed the presence of filaments, significantly thinner than flagella and often bundled, associated with cell surfaces and shed into the external milieu. In-frame deletion mutations of all of the ctp genes, with the exception of ctpF, resulted in nonpiliated derivatives. Mutations in ctpA (a pilin homologue), ctpB, and ctpG decreased early attachment and biofilm formation. The adherence of the ctpA mutant could be restored by ectopic expression of the paralogous pilA gene. The ΔctpA ΔpilA double pilin mutant displayed a diminished biovolume and lower biofilm height than the wild type under flowing conditions. Surprisingly, however, the ctpCD, ctpE, ctpF, ctpH, and ctpI mutants formed normal biofilms and showed enhanced reversible attachment. In-frame deletion of the ctpA pilin gene in the ctpCD, ctpE, ctpF, ctpH, and ctpI mutants caused the same attachment-deficient phenotype as the ctpA single mutant. Collectively, these findings indicate that the ctp locus is involved in pilus assembly and that nonpiliated mutants, which retain the CtpA pilin, are proficient in attachment and adherence.